Response of guava (Psidium guajava L.) softwood cuttings to paclobutrazol application in different rooting media - Qadri, Rashad; Akram, M Tahir; Khan, Imran; Azam, Muhammad; Nisar, Numrah; Ghani, M Awais; Tanveer, Mohsin; Khan, MM (Bangladesh Journal of Botany, 2018)
The scope of clonal propagation of guava (Psidium guajava L.) by soft wood cuttings collected from mature plant is described. The most successful media among those traditionally used and to identify promising alternatives was determined. Soft wood cuttings were done to determine the most successful medium and Paclobutrazol (PBZ) hormone concentration. Guava soft wood cuttings were treated with 0, 200, 400 and 600 mg/l PBZ solution and planted in three different rooting media (sand, silt and top soil) and rooted in low-tunnel. The cuttings were allowed to grow under low-tunnel for three months to assess the rooting capability and shooting competency. The study revealed that the species has a great potential for clonal propagation through soft wood cuttings.